Exploratory study on effectiveness usage of office automation system by government sector in rural area / Khairul Izwan Roslan - Roslan, Khairul Izwan (2014)
The growth of IT technology has given opportunities to organization to improve their way to manage their business. By adapting and using some of technology in office environment enabled the organization simplifies their day to day operations. The problems of technology divide may happen in office that located in rural area especially in office automation tools. This research focused on the effectiveness of usage office automation at government sector in rural area. There are two objectives in this research which the first objective is to identify the office automation tools that currently use by selected rural area government agency in office management perspective. The second objective of this research to evaluate the effectiveness of office automation tools usage in selected rural area government agency. They also evaluated the level of usage in using office automation tools in their workplace. Technology Acceptance Model (TAM) is used as the model to collect and evaluate the data from this research. There are some techniques such as questionnaire, observation and interview session is used to collect the data for this research. From this research, it found that the selected government agency has equipped with the latest office automation tools. Then, it found that they are effectively used the office automation tools for their day to day operation. But in terms of application, some of the application is not used effectively by staff in selected government agency which the factors such as lack of training contributed to this factor. The knowledge and experience in using this tool may effect the implementation of this tool in organization.